Synthesis of Co-Cu/La2O3 Pervoskites for Hydrogenation of CO - Tien Thao, Nguyen (Asian Journal of Chemistry, 2013)
Two families of LaCo1-xCuxO3-d perovskites were synthesized by the conventional citrated complex and milling method. An introduction of copper in perovskite lattice gives rise to a slightly distorted structure of LaCoO3 and influences the perovskite reducibility. Temperature programmed reduction analysis indicates the reduction of Co3+, Cu2+ respectively to Co2+ and metallic copper over conventional samples at 310-580 ºC while that on ground perovskites in the temperature range of 320-610 ºC. The reduction of La(Co,Cu)O3 yields a finely dispersed bimetal on a La2O3 support. The proximity of Co3+ and Cu2+ in perovskite structure leads to the formation of cobalt-copper alloy after reduction, which acts as active sites for the hydrogenation of CO into alcohols and hydrocarbon products.